1997
DOI: 10.1002/cbm.174
|View full text |Cite
|
Sign up to set email alerts
|

The association of early risk factors to opiate addiction and psychological adjustment

Abstract: It is clear that family/parental peer and individual risk factors that appear early in life contribute to increased susceptibility to addiction. This study aimed to determine the relationship between those risk factors, the development of opiate addiction, and the development of psychological maladjustment in addicts. A total of 252 subjects were selected from in and around Baltimore, aged less than 40 years, and 12 or older at the onset of opiate addiction. There were 342 controls from the same neighbourhood,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The temporal order of initiation of illegal activities and drug use is crucial in understanding the progression of addiction and criminal careers (Nurco, Hanlon, O'Grady, & Kinlock, 1997a). The fact that onset of illegal activities before onset of weekly drug use was also associated with delayed age of escalated drug use means that individuals initiating crime early in their life may be experimenters during the early stages of their addiction careers.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal order of initiation of illegal activities and drug use is crucial in understanding the progression of addiction and criminal careers (Nurco, Hanlon, O'Grady, & Kinlock, 1997a). The fact that onset of illegal activities before onset of weekly drug use was also associated with delayed age of escalated drug use means that individuals initiating crime early in their life may be experimenters during the early stages of their addiction careers.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Polydrug use and high unemployment have been associated with criminality (Blumstein & Cohen, 1987), and onset of criminal activity before weekly drug use is associated with a wider array of crimes committed (Farabee, Joshi, & Anglin, 2001). The temporal order of initiation of illegal activities and drug use is crucial in understanding the progression of addiction and criminal careers (Nurco, Hanlon, O'Grady, & Kinlock, 1997a). The fact that onset of illegal activities before onset of weekly drug use was also associated with delayed age of escalated drug use means that individuals initiating crime early in their life may be experimenters during the early stages of their addiction careers.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For the baseline version of this instrument, which elicits personal historical data and for which accuracy of recall covering extended time periods is critical, interviewers were trained to structure the interview around significant life events, with temporal reference points to facilitate recall, in keeping with procedures used successfully by the authors and their colleagues at Friends Research Institute (FRI) in previous research studies (e.g., Nurco, Balter, & Kinlock, 1994; Nurco, Hanlon, O’Grady, & Kinlock, 1997). The crime data, which are the focus of the present analyses, were obtained from this questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…A structured interview, in use in our previous and current research (Gordon, Kinlock, Schwartz, & O’Grady, 2008; Kinlock et al, 2007), was utilized at baseline to obtain more detailed historical—and, in some cases, current—information than obtained with the ASI regarding drug and alcohol use, psychological problems, criminality, criminal justice system, supervision and sanctions, legitimate employment, and substance abuse treatment. For the baseline version of this instrument, which elicits personal historical data and for which accuracy of recall covering extended time periods is critical, interviewers were trained to structure the interview around significant life events, with temporal reference points to facilitate recall, in keeping with procedures used successfully by the authors and their colleagues at Friends Research Institute (FRI) in previous research studies (e.g., Nurco, Balter, & Kinlock, 1994; Nurco, Hanlon, O’Grady, & Kinlock, 1997). The crime data, which are the focus of the present analyses, were obtained from this questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Implementing user involvement within the substance misuse field is, however, unlikely to be straightforward. Over the years, many authors have portrayed drug users as impatient, manipulative and aggressive, and identified hostility and anger as typical drug user characteristics [14][15][16][17][18][19]. Indeed, De Leon has argued that drug users 'often display an extreme sense of entitlement and exaggerated reactions to perceived unfairness, a need for immediate gratification in the form of instant answers, resistance through arguments, and a tendency to manipulate authority figures' [20].…”
Section: Introductionmentioning
confidence: 99%